Efficacy and Safety of Para Cervical Block in Manual Vacuum Aspiration (MVA) - in Low Resource Setting (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective (s): To determine the safety and effectiveness of para-cervical block for cervical dilatation and uterine evacuation by MVA.Materials and methods: This descriptive (cross-sectional) study was conducted in a low resource set-up at Homna, Upzilla Health Complex Comilla between January 2016 and June 2016. Forty five patients of 1st trimester incomplete abortion of 12 weeks gestation were the target population for manual vacuum aspiration (MVA) for this study. All patients received para cervical block before MVA procedure. Three minutes after application of block, suction and evacuation of uterus was done. Perioperative oral analgesic (Ibuprofen) and anxiolytic (diazepam) were used 30 minutes before procedure in all patients. Before the procedure, all the women were asked to evaluate the level of pain on a visual analog scale ranged from 0-10. Thirty minutes after the procedure, the patient was asked to describe the pain that she had been feeling during MVA by using the same visual analog scale. Visual analog scale was described by: no pain (0 points), slight pain (1-3 points), moderate pain (4-6 points) and severe pain (7-10 points). Patients were followed up for 7 days and were evaluated for complications before leaving the facility and on the 7th day after procedure. A routine USG of lower abdomen was done on 7th post-evacuation day in all patients, which revealed completeness of the procedure. Informed consent was taken from all the patients.Results: All were first trimester incomplete abortion cases. MVA was performed with para cervical block. Para cervical block reduced pain sensation on cervical dilatation. According to VAS 30 (66.67%) patients had mild pain, 3(6.67%) patients had moderate pain and 12(26.67%) patients had no pain during the procedure. Six (13.33%) patients had mild pain and others had no pain after the procedure. There was no severe pain before or after the procedure. Thirty (75.56%) patients discharged before 4 hours and 11 (24.44%) patients discharged after 4 hours of the procedure. No patients had any complications like pervaginal bleeding, infection or retention of product. The cost was minimum and patients satisfaction was high.Conclusion: Paracevical block is effective in reducing pain sensation during MVA with a reasonable cost of the procedure.Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 70-74